Sustainability assessment for an offshore coral reef island based on scenario simulation and emergy analysis - Wu, Wenzhou; Zhang, Peng; Jiang, Huiping; Su, Fenzhen (Frontiers in Marine Science, 2023)
As the scale and intensity of ocean spatial exploitation increase, the development of offshore island tourism has been thriving, and meanwhile the utilization of uninhabited islands is also attracting more and more attention. In order to achieve the sustainable development of offshore island tourism and the scientific and reasonable utilization of uninhabited island natural resources, it is important to evaluate the population carrying capacity of this specific type and conduct the corresponding sustainability assessment. To this end, we proposed a quantitative evaluation method for the sustainable development of offshore coral reef island based on scenario simulation and emergy analysis. This method was tested on a coral reef island in the South China Sea, namely the Lingyang Reef. Different scenarios were simulated to reveal the dynamics in emergy structure of Lingyang Reef, and the sustainable development capability of the Lingyang Reef system was quantitatively analyzed under different scenarios, providing a quantitative basis for the sustainability assessment of ecotourism on offshore coral reef island. Results showed that (1) when accommodating 2000 persons, the island system was in a low load state, with sustainable values in terms of renewable energy input percentage, environmental load ratio, and emergy sustainable index, except for the critical state of the emergy yield ratio; (2) when accommodating 5000 persons, the emergy yield ratio was in an unsustainable state, with the emergy sustainable index in a critical state, and both of the renewable energy input percentage and environmental load ratio in sustainable states, indicating that the current socioeconomic activities were not beyond the carrying capacity, and the development and utilization of island resources were moderate; (3) when accommodating 10000 persons, the renewable energy input percentage and emergy sustainable index were in critical states, and the emergy yield ratio and environmental load ratio were in unsustainable states, indicating that the corresponding human activities had exceeded the carrying capacity.